PERBANDINGAN HASIL TERAPI PREDNISON TUNGGAL DAN KOMBINASI DENGAN ASIKLOVIR PADA BELLS PALSY - Rosalina Febby Arifin*, Nani Kurniani**, Suryani Gunadharma** (NEURONA, 2009)
BACKGROUND HSV TYPE 1 REACTIVATION WAS THOUGHT TO BE THE ETIOLOGY OF FACIAL NERVE INFLAMMATION WHICH IS CAUSED BELLS PALSY SO THAT CLINICIANS TRY TO GIVE ACYCLOVIR AND PREDNISONE